DEPENDENCE LIPID ABNORMALITIES IN PATIENTS WITH HYPERTENSION ON THE LEVEL INFLAMMATION - Заремба, Є.Х.; Virnaya, M.M. (World of Medicine and Biology, 2016)
This article is devoted to studying the links between lipid spectrum of the blood and systemic inflammation. Positive correlations between indicators of systemic inflammation and blood pressure indicate inflammation involved in the pathogenesis of hypertension and target organ damage. Established relationships between indicators of systemic inflammation and lipidohramy indicate metabolic conditioning units hyperactivity cytokine immunoregulation.